Software architecture: foundations, theory, and practice - Medvidovic, Nenad; Taylor, Richard N. (2010 ACM/IEEE 32nd International Conference on Software Engineering, 2010)
Software architecture has become a centerpiece subject for software engineers, both researchers and practitioners alike. At the heart of every software system is its software architecture, i.e., "the set of principal design decisions about the system". Architecture permeates all major facets of a software system, for principal design decisions may potentially be made at any time during a system's lifetime, and potentially by any stakeholder. Such decisions encompass structural concerns, such as the system's high-level building blocks---components, connectors, and configurations; the system's deployment; the system's non-functional properties; and the system's evolution patterns, including runtime adaptation. Software architectures found particularly useful for families of systems---product lines---are often codified into architectural patterns, architectural styles, and reusable, parameterized reference architectures. This tutorial affords the participant an extensive treatment of the field of software architecture, its foundation, principles, and elements, including those mentioned above. Additionally, the tutorial introduces the participants to the state-of-the-art as well as the state-of-the-practice in software architecture, and looks at emerging and likely future trends in this field. The discussion is illustrated with numerous real-world examples. One example given prominent treatment is the architecture of the World Wide Web and its underlying architectural style, REpresentational State Transfer (REST).